Implementation of Law No. 38 of 2004 on Roads in Handling Damaged Roads in Serang District and the Responsiveness of the Department of Public Works and Spatial Planning of Serang City - Mumun Komala Sari; Try Adhi Bangsawan; Dede Qodrat Al-Wajir (Journal of Innovative and Creativity (Joecy), 2026)
Law No. 38 of 2004 on Roads governs local government authority and responsibility in road administration, including the handling of damaged roads. In Serang District, road damage still occurs even though most city roads are in good condition, requiring a prompt response from the Department of Public Works and Spatial Planning (DPUPR) of Serang City. This study aims to analyze the implementation of Law No. 38 of 2004 in handling damaged roads in Serang District, to identify its supporting and hindering factors, and to examine the responsiveness of DPUPR Serang City in addressing public complaints. The study employed a qualitative approach using the case study method. Key and supporting informants were selected through purposive sampling. Data were collected through observation, interviews, and documentation, analyzed through data reduction, data display, and conclusion drawing, and validated through source triangulation, method triangulation, and member checking. Using the Van Meter and Van Horn implementation model, the results show that the implementation of Law No. 38 of 2004 has been carried out but is not yet optimal: policy standards and objectives are clear but constrained by budget limitations; technical resources are adequate, yet supporting facilities such as drainage and street lighting remain limited; the organizational structure is in place, though its execution in the field is not fully consistent; internal communication runs well, while communication with the public remains reactive; and the implementers' disposition is positive but its effectiveness is limited by resource constraints. DPUPR's responsiveness to public complaints tends to be reactive and uneven, as reports that go viral on social media are generally followed up faster than those submitted through formal channels. It can be concluded that the implementation of the damaged-road-handling policy in Serang District has not run optimally due to budget constraints and a still-reactive response pattern, despite being supported by clear authority distribution and the commitment of the implementing officials.